Constitutional reform and its impact on TVET governance in Nepal: A report in support of developing understanding and finding the way forward for federalizing the TVET sector in Nepal - Ursula Renold; Katherine Caves (ETH Zurich, KOF Swiss Economic Institute, 2017)
This report maps out how Nepal's new constitution (NC) explicitly and implicitly foresees the federalization of the technical vocational education and training (TVET) sector, and outlines how that sector can best be federalised. Our goal is to broaden the understanding of key stakeholders in the Nepali TVET sector on the issues of equitable, effective and efficient TVET services in a federalised context. The insights in this report are based on consultation with key leaders and stakeholders in Nepal's TVET system, along with current research and scholarship on TVET governance plus the expert's own experiences with constitutional reforms and TVET federalization in Switzerland and Germany.
Keywords: 330